Acute profound thrombocytopenia induced by tirofiban in stent assisted embolization of intracranial ruptured aneurysm-a rare case report. Issue 4 (April 2023) - Piao, Bingda; Li, Tong; Zhong, Hongliang; Yang, Hongchao; Wang, Yang; Liu, He
Abstract: Objectives: Glycoprotein (GP) IIb/IIIa receptor antagonists (Tirofiban) are often used as antiplatelet agents in patients undergoing interventional therapy due to acute coronary syndrome and cerebrovascular diseases. Thrombocytopenia is a common complication of GP IIb/IIIa receptor antagonist, with an incidence of 1%–5%, whereas acute profound thrombocytopenia (platelet count<20 × 109/L) is extremely rare. We reported a case of acute profound thrombocytopenia due to tirofiban treatment to inhibit platelet aggregation during and after surgery in a patient who underwent stent-assisted embolization for ruptured intracranial aneurysm. Case presentation: A 59-year-old female patient, who visited the Emergency Department of our hospital due to sudden headache, vomiting, and unconsciousness for 2 hours. Neurological examination: the patient was unconscious, the pupils on both sides had the same roundness, and the reflection on light was slow. The Hunt-Hess grade was IV. Head CT showed subarachnoid hemorrhage and Fisher's score was 3. We immediately implemented LVIS stent-assisted embolization, intraoperative heparinization, and intraoperative jailing technology to perform dense embolism on aneurysms. The patient was treated with mild hypothermia and Tirofiban 5mL/h intravenous pump. Since then, the patient had developed acute profound thrombocytopenia. Conclusion: We reported a case of acute profound thrombocytopenia due to tirofiban treatment during and after interventional therapy. For patients after unilateral nephrectomy, we should pay more attention to avoid the occurrence of thrombocytopenia caused by abnormal metabolism of tirofiban, although the Laboratory examination showed normal results.